Optimalisasi Program Permaculture Melalui Adaptasi dan Mitigasi Berbasis Kearifan Lokal di Kelurahan Rejowinangun Selatan - Alifia Revan Prananda; Mohammad Norman Aulia Mufasir; Nabila Fairuzzahra; Niken Orisa Putri; Anisa Lestari (Lembaga Pengembangan Kinerja Dosen, 2024)
The southern district of Rejowingan in Magelang faces challenges like large dumpstores, poor water quality, floods, and rising food needs. Villagers are working with the Ormawa DPM KM PPK team to address these issues. The government launched the Climate Village Program to improve the region's climate and resilience to natural disasters. Permaculture principles can be applied to organic waste management through maggot cultivation, which reduces waste volume and supports sustainable agriculture. This combination of permaculture and maggot cultivation can be an effective and environmentally friendly model for addressing organic waste and ecosystem sustainability.